The Role of Traditional Medicine in Health Justice: Balancing Indigenous Practices and Modern Healthcare (Indonesian Health Justice Review, 2024)
In Indonesia, traditional medicine remains a crucial aspect of healthcare, particularly in rural and indigenous communities. This paper explores the role of traditional medicine in promoting health justice, while analyzing the challenges of integrating indigenous practices with the formal healthcare system. The study utilizes a mixed-methods approach, including interviews with traditional healers, healthcare practitioners, and patients, along with a review of policy documents related to the regulation of traditional medicine. Findings reveal that traditional medicine is widely used and trusted by many Indonesians, especially in rural areas where access to modern healthcare is limited. However, there are concerns about the lack of regulation, safety standards, and the potential for conflict between traditional healing practices and evidence-based medicine. The paper argues for a more inclusive approach that respects cultural practices while ensuring patient safety and efficacy. Recommendations include the establishment of regulatory frameworks that integrate traditional medicine with modern healthcare, promote training for healthcare professionals in cultural competence, and support research into the safety and efficacy of traditional healing practices.